(untitled) (The Review of Diabetic Studies, 2025)
Diabetes mellitus is a chronic metabolic condition associated with significant morbidity and mortality, with acute complications such as hypoglycemia, diabetic ketoacidosis (DKA), and hyperosmolar hyperglycemic state (HHS) contributing to a substantial proportion of prehospital emergency calls worldwide. Paramedics, often the first point of medical contact, play a critical role in the recognition, assessment, and management of these emergencies. This review explores the epidemiology of diabetic emergencies, the physiological underpinnings relevant to prehospital interventions, and the impact of timely paramedic management on patient outcomes. Key strategies discussed include rapid glucose administration for hypoglycemia, supportive care and fluid resuscitation for hyperglycemic crises, and the importance of structured protocols in guiding clinical decision-making. The review further highlights variations in scope of practice across regions, challenges in non-transport decisions, and innovations such as telemedicine, point-of-care testing, and artificial intelligence integration in ambulance services. Training, simulation, and community paramedicine initiatives are emphasized as crucial for enhancing care quality and reducing healthcare burden. Effective prehospital diabetes management by paramedics is essential in mitigating complications, optimizing patient outcomes, and improving system-wide efficiency.